Targeted and multifunctional arene ruthenium chemotherapeutics - Smith, Gregory S.; Therrien, Bruno (My University, 2011)
A review. The introduction of multifunctionalities for tumor targeting is becoming a popular strategy toward the development of new therapeutic agents. In particular, the multifaceted potential of ruthenium(ii)-arene complexes show great promise as chemotherapeutics. An ever-increasing no. of papers dealing with the integration of ruthenium complexes with biol. active mols. to derive bioorganometallic mols. of chemotherapeutic significance have been published in recent years. This perspective review presents a short overview of multifunctional ruthenium-based drugs, esp. those contg. arene ruthenium complexes, with the emphasis on the combination of photosensitizers with ruthenium complexes for the prepn. of novel multifunctional photodynamic therapy agents. [on SciFinder(R)]
Keywords: review ruthenium complex antitumor photodynamic therapy